Cost‐Effectiveness Modeling of Repetitive Transcranial Magnetic Stimulation Compared to Electroconvulsive Therapy for Treatment‐Resistant Depression in Singapore. Issue 4 (16th November 2017) - Zhao, Ying Jiao; Tor, Phern Chern; Khoo, Ai Leng; Teng, Monica; Lim, Boon Peng; Mok, Yee Ming
Abstract : Background: Compared to electroconvulsive therapy (ECT), the cost‐effectiveness of repetitive transcranial magnetic stimulation (rTMS) in the management of treatment‐resistant depression (TRD) remains unclear. Objective/Hypothesis: This study evaluated the cost‐effectiveness of rTMS vs. ECT for TRD from Singapore societal perspective. Methods: We constructed a Markov model to project the cost and benefit of rTMS compared with ECT over one year in patients with TRD. The relative treatment effects between rTMS and ECT were obtained from meta‐analyses of published trials. The effectiveness and quality of life data for patients using ECT, resource use for TRD and their associated costs were derived from the national tertiary mental institution in Singapore. Results: At one year, rTMS was cost‐effective relative to ECT. The incremental cost‐effectiveness ratio (ICER) associated with ECT was Singapore dollars (SGD) 311, 024 per quality‐adjusted life‐year (QALY) gained. This exceeded the willingness‐to‐pay threshold of SGD 70, 000 per QALY gained. A similar trend was observed for ICER per remission achieved (i.e., SGD 143, 811 per remission achieved with ECT). In the subgroup analysis, rTMS was found to be less costly and more effective than ECT in nonpsychotic depressive patients. In the scenario analysis, ECT employed as an ambulatory service yielded a much smaller ICER (i.e., SGD 78, 819 per QALY gained) compared to the standard inpatient setting. Conclusions: rTMS was a cost‐effective treatment compared to ECT in TRD over one year. The cost‐effectiveness of rTMS was attenuated when ECT was used in the outpatient setting.